Dialogic theology of missions as a response to the global refugee phenomenon - Shakespeare Sigamoney; Samuel K.B. Nkrumah-Pobi (HTS Teologiese Studies/Theological Studies)
The legacies of colonialism on both the colonised and coloniser is one thing that our world cannot escape in contemporary times. In most of the places, colonialism came with its own form of Christianity. This colonial Christianity was based on the idea of exclusion, homogenisation and conquering the other. Thus, the combination of the ideals of colonialism and Christianity brought about a type of nationalism, which was monologic. This monologic nationalism as an ideology not only creates refugees but also generates a monological ‘unity’ among the people in the country of arrival against these refugees. This poses a danger to humanity as a whole. Thus, it is important for scholars of religion and theology to deconstruct ideas on the line of monologic nationalism and embrace a form of nationalism that is dialogical in nature. In this regard, this article using Mikhail Bakhtin’s idea of dialogism as its framework attempts to construct a dialogic theology of missions as a response to the global refugee phenomenon. The article argues that there must be a shift from colonial missions, which are monologic in nature to a dialogic theology of missions grounded in World Christianity.